2, 6-Dibromogallates as a new building block for controlling π-stacking, network formation and mirror symmetry breaking. Issue 53 (8th June 2021) - Kwon, Ohjin; Cai, Xiaoqian; Saeed, Azhar; Liu, Feng; Poppe, Silvio; Tschierske, Carsten
Abstract : Bromination of the gallate unit changes the π-stacking mode, widens LC ranges and favors mirror symmetry broken triple networks over double networks. Abstract : Achiral multi-chain (polycatenar) compounds based on the 2, 7-diphenyl substituted [1]benzothieno[3, 2- b ]benzothiophene (BTBT) unit and a 2, 6-dibromo-3, 4, 5-trialkoxybenzoate end group lead to materials forming bicontinuous cubic liquid crystalline phases with helical network structures over wide temperature ranges.